Customer Discovery is Necessary for the Development of Artificial Intelligence-based Solutions in Orthopedic Surgery - Alireza Ebrahimi; Soheil Ashkani-Esfahani (Journal of Foot and Ankle Surgery (Asia Pacific))
The applications of artificial intelligence (AI) in both clinical practice and biomedical research have been expanding remarkably during the past few decades. Although billions of dollars have been spent on AI technologies, human is still dealing with the hype of AI and have relatively failed to realize the real uses of this technology and utilize it in the most cost-effective pathway. Customer discovery helps developers make hypotheses about potential customers, update and change their value propositions, find possible revenue streams, and make a draft of their business plan.